Dīwān-i Ghiyāth al-Dīn-i Kujujī - Kujujānī, Khwājah Ghiyāth al-Dīn Shaykh Muḥammad, (Miras Maktoob, ISBN: 9789004365452., 2019)
Born into an influential family from Kujuj near Tabriz, Khwājah Ghiyāth al-Dīn Shaykh Muḥammad Kujujānī was a relative of the well-known mystic Muḥammad b. Ṣiddīq Kujujī (d. 677/1278). Better known as Khwāja Shaykh, Kujujānī held the office of Shaykh al-Islām of Tabriz under the Jalāyirid rulers Shaykh Uways (d. 776/1374) and his son Ḥusayn. Like his forebear, Khwāja Shaykh had Sufi leanings and possessed a flourishing khānqāh (Sufi convent) in Tabriz. In 783/1382, Shaykh Ḥusayn was killed by his brother Aḥmad (d. 813/1410). Under Aḥmad, Khwāja Shaykh was still a man of importance, at ease among governors and heads of state, which is clear from his involvement in Aḥmad's negotiations with some of his enemies. However, fearing Khwāja Shaykh's influence as a spiritual leader, Aḥmad had him murdered in 787/1385 or 788/1386. Popular in Azerbaijan and Iraq in his lifetime, Khwāja Shaykh's poetry is published here for the first time. Contains material in Fahlawī (Azeri)